Analisa Usability Test pada Website Siori Menggunakan Metode Heuristic Evaluation - Setiyadi; Agus Yulianto (Politeknik Ganesha Medan, 2023)
This research is to analysis level of usability on the SIORI website (Organization and Home Information System) measured based on heuristic evaluation method using 10(ten) variables heuristicnthat meet the usability criteria. The population of this study are Buddhist Religious Organizations (OKB) and Buddhist Religious Houses of Worship (RIAB) in DKI Jakarta Province. The sample in this study consisted of 47 OKB and 50 RIAB, using probability sampling, simple random sampling and proportionate stratified random sampling as data collection techniques. Research data was collected using a questionnaire and analyzed using descriptive analysis method. The analysis technique uses multiple linear regression and the assessment uses a Likert scale. The results of the normality and linearity tests on the Heuristic Evaluation model state that they are normal and linear. The results of the multiple linear regression test in the Heuristic Evaluation model have a simultaneous influence between the independent variables consisting of (1) Visibility of System Status, (2) Match Between System and the Real World, (3) User Control and Freedom, (4) Consistency and Standards, (5) Error Prevention, (6) Recognition Rather Than Recall, (7) Flexibility and Efficiency of Use, (8) Aesthetic and Minimalist Design, Help Users Recognize, (9) Diagnose and Recovers From Errors, (10) Help and Documentation together (simultaneously) on usability. From this analysis it is hoped that it can become a recommendation or benchmark for website developers and managers to improve the quality of the SIORI website. Keywords: usability, heuristic evaluation, SIORI website Abstrak- Penelitian ini bertujuan untuk mengalisis tingkat usability pada website SIORI (Sistem Informasi Organisasi dan Rumah) yang diukur menggunakan metode heuristic evaluation dengan menggunakan 10 Variabel heuristic evaluation yang memenuhi kriteria usability. Populasi penelitian ini adalah Organisasi Keagamaan Buddha (OKB) dan Rumah Ibadah Agama Buddha (RIAB) di Provinsi DKI Jakarta. Sampel dalam penelitian ini terdiri dari 47 OKB dan 50 RIAB, menggunakan probability sampling, simple random sampling dan proportionate straified random sampling sebagai teknik pengambilan data. Data penelitian dihimpun menggunakan kuisioner dan dianalisis dengan metode analisis deskriptif. Teknik analisis menggunakan regresi linear berganda dan penilaian menggunakan skala likert. Hasil pengujian normalitas dan linearitas pada model Heuristic Evaluation menyatakan normal dan linear. Hasil uji regresi linear berganda pada model Heuristic Evaluation ada pengaruh secara simultan antara variabel bebas yang terdiri dari (1) Visibility of System Status, (2) Match Between System and the Real World, (3) User Control and Freedom, (4) Consistency and Standards, (5) Error Prevention, (6) Recognition Rather Than Recall, (7) Flexibility and Efficiency of Use, (8) Aesthetic and Minimalist Design, Help Users Recognize, (9) Diagnose and Recovers From Errors, (10) Help and Documentation secara bersama-sama (simultan) terhadap usability. Dari analisis ini diharapkan bisa menjadi rekomendasi atau tolak ukur bagi pihak pengembang dan pengelolah website untuk meningkatkan kualitas website SIORI. Kata kunci: usability, heuristic evaluation, website SIORI